Complex Resistivity of Shaly Sandstone: Study on Pressure and Saturation Effect - Khairy, Hilfan (IJENS pubsliher, 2010)
Measurement of complex resistivity was accomplished on shaly sandstones in low to medium frequency range from 1 Hz until 0.2 MHz. The experiment was conducted at any different partial water brine saturation and different confining pressure. Interfacial and water saturation were observed to evaluate their effect to electrical resistivity. It is found that a pore geometry change due to pressure is recognizable only by using imaginary resistivity rather than real resistivity in low water saturation. This reflects that confining pressure influence a small defect to pore geometry. Meanwhile, bulk volume conductivity is more dominant in high water saturation degree, thus the interfacial conductivity contribution become less important. Relaxation time and its distribution are then estimated by using joint inversion of real and imaginary resistivity. Cole-Cole model inversion is applied to obtain those parameters. It is applied the integration of Lavenberg-Marquardt and Singular Value decomposition (SVD) to avoid singularity problems. The result exposes time distribution decreases as confining pressure is increased from 1000 psi until 3000 psi.